DETERMINANTS OF RETURN ON EQUITY: A COMPARATIVE STUDY OF BANK MANDIRI, BNI, AND BTN USING A PANEL DATA MODEL APPROACH - Juliana, Sherlin; Hidayat, Agus Maolana (Journal of Posthumanism, 2025)
This study aims to analyze the determinants of Return on Equity (ROE) as a measure of profitability in three state-owned banks in Indonesia: Bank Mandiri, BNI, and BTN. The independent variables used in this research include Net Profit Margin (NPM), Total Asset Turnover (TATO), interest rate, and Operating Expenses to Operating Income ratio (BOPO). The study employs secondary data derived from annual financial statements covering the 2015–2024 period. The analysis was conducted using panel data regression with the Random Effect Model (REM), selected based on the results of the Chow and Hausman tests, and processed using the EViews 12 statistical software.The findings reveal that NPM and TATO have a positive and significant effect on ROE. Specifically, a 1% increase in NPM increases ROE by 0.42%, while a one-time increase in TATO improves ROE by 0.15%. Conversely, both BOPO and interest rate exhibit a significant negative effect on ROE, with a 1% increase in BOPO reducing ROE by 0.28% and a 1% increase in interest rate decreasing ROE by 0.21%.The comparative analysis shows that Bank Mandiri recorded the highest average ROE during the study period at 22.8%, followed by BNI at 15.4% and BTN at 9.6%. These results highlight differences in operational efficiency, asset management strategies, and responsiveness to external macroeconomic factors among the three banks. This study is expected to provide practical insights for the formulation of profitability and efficiency enhancement strategies for state-owned banks, as well as serve as a reference for regulators and investors in addressing challenges within the evolving financial and digital landscape.